If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -2) = 2x + -6 Reorder the terms: 2(-2 + x) = 2x + -6 (-2 * 2 + x * 2) = 2x + -6 (-4 + 2x) = 2x + -6 Reorder the terms: -4 + 2x = -6 + 2x Add '-2x' to each side of the equation. -4 + 2x + -2x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 0 = -6 + 2x + -2x -4 = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 = -6 + 0 -4 = -6 Solving -4 = -6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2x-8x+4=x-9+13 | | 3x-14=3x-14 | | 1.1x+8=0.5x+20 | | 1.1x+8=0.5x+29 | | (20-2x)x=90 | | 5227.50=5100(1+.025r) | | y=9.5+100 | | y=-0.62+0.0005x | | y=-0.62+0.0005211x | | y=0.0005211x+-0.62 | | 2c+4+3c=-16 | | 2x^2+1=2x+12 | | 4y-5x=40 | | .6x+1.9x=5 | | .6x+1.9=5 | | 2x^2+43x-2730=0 | | a+5=3 | | 7-6(3-8x)=0 | | x^2-14x+36= | | log(100)=10 | | ?10x+1+7x=37 | | ?10x+1+7x=32 | | ?10x+1+7x= | | ?10x+1+7x=37 | | log(x+5)-log(1-5x)=0 | | .50(x-6)+1=2(x-10)-3 | | 6x+4+8x+18+(180-20x+4)=180 | | 10y-x= | | 3w-10=50 | | log(x+5)=log(1-5x) | | 16n^2-24n+9= | | 4x-(6x-4)= |